2017
DOI: 10.1186/s40168-017-0336-9
|View full text |Cite
|
Sign up to set email alerts
|

Profiling bacterial communities by MinION sequencing of ribosomal operons

Abstract: BackgroundAn approach utilizing the long-read capability of the Oxford Nanopore MinION to rapidly sequence bacterial ribosomal operons of complex natural communities was developed. Microbial fingerprinting employs domain-specific forward primers (16S rRNA subunit), reverse primers (23S rRNA subunit), and a high-fidelity Taq polymerase with proofreading capabilities. Amplicons contained both ribosomal subunits for broad-based phylogenetic assignment (~ 3900 bp of sequence), plus the intergenic spacer (ITS) regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
83
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 35 publications
1
83
0
Order By: Relevance
“…The Oxford Nanopore MinION is a portable sequencing device that has recently emerged as a rapid and cost-effective sequencing platform that produces long reads, and has multiple applications in clinical microbiology, such as pathogen detection [36], bacterial genome assembly [37] and plasmid and resistance gene detection [38,39]. Specific to microbiome analysis, the utility of the MinION platform has been demonstrated in rRNA amplicon-based sequencing [40][41][42] and in metagenomics for outbreak analysis of bacteria [43] and viruses [44].…”
Section: Discussionmentioning
confidence: 99%
“…The Oxford Nanopore MinION is a portable sequencing device that has recently emerged as a rapid and cost-effective sequencing platform that produces long reads, and has multiple applications in clinical microbiology, such as pathogen detection [36], bacterial genome assembly [37] and plasmid and resistance gene detection [38,39]. Specific to microbiome analysis, the utility of the MinION platform has been demonstrated in rRNA amplicon-based sequencing [40][41][42] and in metagenomics for outbreak analysis of bacteria [43] and viruses [44].…”
Section: Discussionmentioning
confidence: 99%
“…The taxonomic profile of the microbiome of the biofilm was studied via 16S rRNA amplicon Nanopore sequencing as well as by sequencing the whole 16S rRNA gene without the need for in silico assembly (Kerkhof et al, 2017). After a quality filtering of the raw reads, a total of 11,163 16S rRNA sequences were retrieved and taxonomically classified.…”
Section: Taxonomic Diversity Of the Microbial Communitymentioning
confidence: 99%
“…In fact, 46.6% of microbial phylotypes were singletons and nine phyla were represented by a single read (Table S1). Nevertheless, a study has recently demonstrated that the MinION technology has the ability to provide rRNA operon sequence data of sufficient quality for characterizing the microbiota of complex environmental samples and provides results that are reproducible, quantitative and consistent (Kerkhof et al, 2017). Another explanation why a high number of phylotypes were identified in the biofilm is that the seed sludge and the feedstock used was carrying a highly diverse microbial load (Kirkegaard et al, 2017), albeit those communities might not be metabolically active in the sampled biomass.…”
Section: Taxonomic Diversity Of the Microbial Communitymentioning
confidence: 99%
“…Long-read sequencing using ONT sequencers has been applied using different approaches to study the genetic content of bacterial samples, such as full-length 16S rRNA gene 1 , rrn operon sequencing [2][3][4] , metagenomics [5][6][7][8][9][10] or Whole Genome Sequencing (WGS) 11,12 . Long-read output can span repetitive regions either from bacteria, archaea or eukarya, thus facilitating the assembly of genomes and the characterization of plasmids, and the location and genomic context of resistance genes 13 .…”
Section: Introductionmentioning
confidence: 99%